Effect of physical activity on anthropometric and physiological parameters in preschool and school-aged children: a systematic review and meta-analysis of randomized controlled trials - Wang, Nina; Wang, Qinglei; Wang, Mengyan; Abdul Rahman, Mohd Nazri Bin (Frontiers in Public Health, 2025)
BackgroundEarly childhood is an essential phase characterized by physical, social, and cognitive development. This developmental stage lays the foundation for establishing lifelong health behavior patterns that can resonate into adolescence and adulthood. Despite the growing recognition of the significance of physical activity during crucial developmental periods, the advent of technology-driven modern society has induced a notable preference among children for a sedentary lifestyle. In addition, compared to research involving older children and adolescents, the existing evidence for preschool and school-based remains relatively limited in scope and depth.ObjectiveTo assess the influence of exercise interventions on anthropometric factors, encompassing Body Mass Index (BMI), skinfold thickness (ST), BMI z-score, and Waist Circumference (WC), as well as physiological parameters, including Diastolic Blood Pressure (DBP) and Systolic Blood Pressure (SBP), in both preschool and school-based children, and the comparison between these two age groups.MethodsFour databases were searched (such as Web of Science, The Cochrane library, Scopus, and Embase) and included only randomized controlled trials (RCTs) assessing exercise interventions’ impact on anthropometric measurements and blood pressure in children aged 1–12 years, including both preschoolers and school-aged children. The analysis used the standardized mean difference as the outcome measure and employed a random-effects model for data analysis.ResultsFrom the results, including 29 RCTs, exercise interventions were linked to favorable reductions: BMI (μ = −0.317; 95% CI: −0.570 to −0.064), WC (μ = −0.010; 95% CI: −0.104–0.085), and ST (μ = −0.066; 95% CI: −0.293–0.161). Also, improvements occurred in DBP (μ = −0.068; 95% CI: −0.139–0.002) and SBP (μ = −0.186; 95% CI: −0.373–0.001). Subgroup analysis found no significant age group differences.ConclusionThis meta-analytical method provides substantial evidence affirming the effectiveness of physical exercise programs, regardless of age group, with a focus on gross motor skills, whether implemented alone or in conjunction with supplementary interventions, in reducing anthropometric parameters.Systematic Review RegistrationPROSPERO 2023 (CRD42023470312).